Scale insects (Hemiptera: Coccomorpha) in coffee roots of Norte de Santander and Valle del Cauca, Colombia, and description of a new species. (2018)
Currently, the hypogeal scale insects (Hemiptera: Coccomorpha) are the second most important problem pest arthropods for Colombian coffee crops. In order to develop integrated pest management programs, it is necessary to identify the species associated with this crop. In this study, 768 specimens from 85 samples collected from coffee roots in Norte de Santander and Valle del Cauca were analyzed. Ten genera belonging to four families were identified. Puto barberi, Toumeyella coffeae and Dysmicoccus varius were the most recurrent species. Dysmicoccus mackenziei, Dysmicoccus radicis and Mixorthezia minima are recorded for first time in Colombia. Coffea arabica is reported to be a new host for Phenacoccus solani and a new species of the genus Pseudorhizoecus is described.